Deathlife, lifedeath. (2nd July 2016) - Bazzano, Manu
ABSTRACT: This paper provides a comparative exploration of mindfulness and therapeutic presence and absence. Drawing from the Buddha's teachings, mindfulness is articulated here as awareness of impermanence rather than as a set of techniques. Drawing from Rogers, Presence is discussed not in mystical terms, but in terms of its valuable, neglected counterparts: absence, entropy, and the Buddhist notion of sunyata.